An Improved Calcination Route to Synthesize Carbon Doped Mesoporous TiO2 and Its Photocatalytic Activity Under Visible Light - Hu, S.Z.; Li, F.Y.; Fan, Z.P.; Zhang, J. (Asian Journal of Chemistry, 2013)
Carbon doped mesoporous TiO2 was prepared by an improved calcination route. X-Ray diffraction, UV-visible spectroscopy, TEM, X-ray photoelectron spectroscopy and nitrogen adsorption were used to characterize the prepared TiO2 samples. Citric acid was used as not only carbon source but also the pore-forming agent. The photocatalytic activities were tested in the degradation of an aqueous solution of a reactive dyestuff, methylene blue, under both UV and visible light. The carbon doped mesoporous TiO2 prepared by improved calcination route showed much higher photocatalytic activity than that of catalyst prepared by conventional calcination route and neat TiO2 under visible light. A possible mechanism for the photocatalysis was proposed.